Modelo estrutural de previsão de preço e volume negociado de minério de ferro - Franco, Patricia Calazans Albuquerque de Mello (2008)
This study presents a forecasting model for prices and volumes traded in the seaborne iron ore market. A VAR model (with endogenous variables with one lag) was developed, using oil prices (Brent) and an industrial production index. After testing for a unit root in the variables and discovering that none of them were stationary, the co-integration test showed that there was a long term relation between them, which was in itself stationary, eliminating the possibility of a spurious regression. As a result, the VAR model was seen to be consistent, with high adherence to forecast prices and volumes for seaborne trade, in spite of some short term imprecision.